2015
DOI: 10.1016/j.bjorl.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vestibular evoked myogenic potentials in children

Abstract: We established normal values of cervical myogenic vestibular responses in children between 8 and 13 years without neurotological complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
7
1
1
Order By: Relevance
“…These results agree with [13] . They studied cervical vestibular myogenic in children aged 8-13 years without otoneurologic complaints, they found that increasing age was accompanied by a significant increase in peak P1 and N1 amplitudes.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with [13] . They studied cervical vestibular myogenic in children aged 8-13 years without otoneurologic complaints, they found that increasing age was accompanied by a significant increase in peak P1 and N1 amplitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Pediatric norms are variable and the test itself is very operator dependant. The normative value the (38) first paper of its kind as regards mean amplitudes and thresholds in children were different from other publications (39,40). It was also emphasized that this variability is due to several factors that include VEMP stimulus parameters and local laboratory norms (39).…”
Section: Audiovestibular Quantificationmentioning
confidence: 88%
“…VEMP studies have shown that third window VEMP characteristics [i.e., increased amplitude and decreased threshold due to hypersensitivity of the saccule and the urticle to acoustic energy ( 19 )] may be observed in third window disorders that include EVA, SSCD, PSCD, and CFD in the pediatric population ( 3 , 46 , 81 , 82 ). We have discussed the variable norms for pediatric cVEMP in our Methods section ( 38 40 ) and the difficulties in performing the test in children. For oVEMPS, there are very few studies ( 83 , 84 ) to establish norms.…”
Section: Discussionmentioning
confidence: 99%
“…The otoneurologist has difficulties obtaining an adequate history and performing an otoneurological examination of children in order to establish the right diagnosis. 6 By stimulating the ear with high-intensity sound, cVEMP has been successfully recorded in newborns aged 3-5 days. oVEMP can be registered in children aged two years and older.…”
Section: Introductionmentioning
confidence: 99%
“…Older children with better developed muscles have higher amplitudes p13 and n23 latencies with cVEMP in children are significantly correlated with age, head circumference, height and body weight. 6 It is preferable to perform the cVEMP test after the age of three months. It is necessary for the childs neck muscles to develop so that it can support its head.…”
Section: Introductionmentioning
confidence: 99%